Language Learning Strategies Used by Students with Different Listening Achievement - Alfuatin, Lilik (ELT Forum: Journal of English Language Teaching, 2019)
The objective of this study was to describe the language learning strategies used by students with different listening achievement. Seventy students from two classes were chosen to participate in this study by using a convenience sampling technique. They were divided into three achievement groups based on the achievement group?s technique by Arikunto (2006). Listening achievement test and modified Strategy Inventory of Language Learning (SILL) questionnaire were used to collect data. The design of this research was descriptive quantitative. The study found that high, intermediate, and low achievement group used all six kinds of strategy. High achievement group used strategies more often than intermediate, and low achievement group. Metacognitive strategies were the most used strategies for high, intermediate, and low achievement group. In contrast, affective strategies were the least used strategies for high, and intermediate achievement group. Meanwhile, compensation was the least used strategy for low achievement group.